Sustainable Teaching: Three urban teachers make a case for teacher education 3.0. (March 2021) - Sutherland, Danielle; Ponnock, Annette R.; Jordan, Will J.; Kuriloff, Peshe; Hoffman, Brooke
Abstract: The purpose of this paper is to present evidence as to the efficacy of teacher education 3.0 aligned teacher preparation. This paper shares narratives of three urban teachers who attended a preservice program that did not emphasize practice-based teacher preparation. These programs placed a greater emphasis on providing their graduates with theoretical frameworks and context for schools in the United States. Drawing on semi-structured interviews, these data underscore both the importance of providing preservice teachers with an understanding of educational history and context, especially as it relates to sustainability and satisfaction in the profession and its limitations. Highlights: Teachers' sense of satisfaction is tied to their evaluations of their preparation. Teacher preparation that does not emphasize a practice-based approach can act as a powerful sustaining force; however, the effect can be undercut without proper supports. Sustained exposure to critical coursework can inform teachers' own orientation towards equitable and just teaching.